Risk Factors to Incidence of Diarrhea in Toddler at Totok Village - Dona, Erniati Timbu; Talahatu, Anna Heny; Toy, Sarci Magdalena (Faculty of Public Health, Nusa Cendana University, 2022)
Diarrhea is a common disease in Indonesia, as a probable sickness of incident which is frequently outbreak by death. In the Southwest Sumba Regency in 2019, there were 9.271 instances of diarrhea spread over twelve Puskesmas operating districts. One of the Puskesmas is Rada Mata Health Center, which has 324 cases dispersed over many communities. Totok Village is one of the areas affected by the diarrhea outbreak, with 64 cases reported. This study aims to examine the factors that contribute to the incidence of diarrhea in children under five in Totok Village, Loura District, Southwest Sumba Regency. The type of research used is analytic observational with a cross sectional research design. The study was conducted in Totok Village, Loura District, Southwest Sumba Regency, in July 2021. The population in this study were all mothers of children under five, who were still active to weigh to the posyandu which were taken at simple random in Totok Village. 2021. The sample in this study was 70 mothers of children under five. The sampling technique was done randomly. Data analysis was performed using the chi-square test with a significance level of 0.05. All variables included mother's level of knowledge (p-value = 0.022), mother's attitude (p-value = 0.017), mother's behavior (p-value = 0.007), history of exclusive breastfeeding (p-value = 0.017), immunization status (p-value = 0.017), value = 0.014), and the availability of latrines (p-value = 0.027), were found to be associated with the incidence of diarrhea in children under five years of age. Therefore, the community, especially mothers of toddlers, should increase their knowledge about preventing diarrhea in children, one of which is providing exclusive breastfeeding to children to increase their immune system.